Mir-223 regulates the number and function of myeloid-derived suppressor cells in multiple sclerosis and experimental autoimmune encephalomyelitis - Cantoni, Claudia; Cignarella, Francesca; Ghezzi, Laura; Mikesell, Bob; Bollman, Bryan; Berrien-Elliott, Melissa M.; Ireland, Aaron R.; Fehniger, Todd A.; Wu, Gregory F.; Piccio, Laura (Acta neuropathologica, 2017)
Myeloid-derived cells play important modulatory and effector roles in multiple sclerosis (MS) and its animal model, experimental autoimmune encephalomyelitis (EAE). Myeloid-derived suppressor cells (MDSCs) are immature myeloid cells, composed of monocytic (MO) and polymorphonuclear (PMN) fractions, which can suppress T cell activities in EAE. Their role in MS remains poorly characterized. We found decreased numbers of circulating MDSCs, driven by lower frequencies of the MO-MDSCs, and higher MDSC expression of microRNA miR-223 in MS versus healthy subjects. To gain mechanistic insights, we interrogated the EAE model. MiR-223 knock out (miR-223 −/− ) mice developed less severe EAE with increased MDSC numbers in the spleen and spinal cord compared to littermate controls. MiR-223 −/− MO-MDSCs suppressed T cell proliferation and cytokine production in vitro and EAE in vivo more than wild-type MO-MDSCs. They also displayed an increased expression of critical mediators of MDSC suppressive function, Arginase-1( Arg1 ), and the signal transducer and activator of transcription 3 ( Stat3 ), which herein, we demonstrate being an miR-223 target gene. Consistently, MDSCs from MS patients displayed decreased STAT3 and ARG1 expression compared with healthy controls, suggesting that circulating MDSCs in MS are not only reduced in numbers but also less suppressive. These results support a critical role for miR-223 in modulating MDSC biology in EAE and in MS and suggest potential novel therapeutic applications.